Population analysis in Perak for area development using D3 tool / Nur Azmina Mohamad Zamani ... [et al.] - Mohamad Zamani, Nur Azmina; Masrom, Suraya; Mohamed Hatim, Shahirah; Ahmad, Zaaba; Yusof, Ahmad Muhyiddin (2020)
In a recent development, the data population has become a trend of analysis that can be valuable to make predictions on any area development. However, the available data on the population are left unstructured and disorganized due to the lack of useful information. Consequences of this problem, it can be hard to analyze the unpredicted data of the population area. This project aims to perform a population analysis in the aspect of specifying suitable property area by deploying the Data-Driven Documents (D3) data visualization method. To achieve this, the objectives of this project are to provide a web platform for analyzing data with the visualization of the D3 tool approach and simultaneously to provide a form of prediction of the population data in the state of Perak, Malaysia on the information visualization. The data of the population are collected from the Department of Statistics Malaysia’s (DOSM) webpage in a form of Comma Separated Value File (CSV). These data were organized to be structured and linked with the map of Perak and geographical coordination information to present the prediction on the future population of Perak state. An Exponential model equation has been used for the prediction method. The benefit of this project is to ease the user to gain useful information about the population in the state of Perak by having early planning for the future development with the population prediction.